Important Elements and Features of Neighborhood Landscape for Aging in Place: A Study in Hong Kong - Shi, Shu-Lin (Frontiers in Public Health, 2020)
With rapid growth in the aging population around the world, the promotion of aging in place has become more significant in recent years. Many neighborhood landscape elements and features have been revealed by accumulating research findings to be critical to aging in place. However, they are usually studied separately or in small groups. Little has been done to examine the relative importance of these elements and features when brought together, from the older adult's point of view. In this context, the current study investigated the perceived importance for older adults of 22 selected neighborhood landscape elements and features. A questionnaire survey was conducted in 17 public rental housing estates in Hong Kong with proportions of older residents (aged 65 or above) between 20 and 40%. According to the 426 collected samples, older adults considered as highly important landscape elements and features that contribute to comfort and help them avoid hazards, such as good ventilation, protection from severe sunshine/rain, body support, and good hygiene, while elements were thought to potentially bring hazards while not being necessities for older adults' outdoor experience were considered least important, including portable chairs, outdoor tables, plants that can be touched, closeness to children's playgrounds, small spaces for solitude, water features, and fitness equipment. After integrally interpreting the findings regarding perceived importance with other collected data, some landscape design suggestions are generated to supplement existing guidelines and recommendations concerning older adults' well-being and quality of life. These findings can inspire future research and landscape design that prioritize promoting aging in place.